A Smart Single‐Loop‐Mediated Isothermal Amplification Facilitates Flexible SNP Probe Design for On‐Site Rapid Differentiation of SARS‐CoV‐2 Omicron Variants - Qijie Lin; Hongchao Gou; Xiaoyun Qu; Kaiyuan Jia; Yuhui Deng; Dan Li; Qianyi Cai; Yucen Liang; Xiaozhen Xu; Yanbin Li; Jianhan Lin; Letian Li; et al. (Advanced Science)
Abstract Rapid on‐site typing methods for SARS‐CoV‐2 variants of concern are crucial for its effective surveillance and control. Herein, a smart single‐loop‐mediated isothermal amplification (ssLAMP) method with the absence of an inner primer but the addition of a swarm primer for differentiation of SARS‐CoV‐2 Omicron variants is developed. This unique primer design strategy offers greater flexibility in introducing single nucleotide polymorphism (SNP) identification probes and enables multiple detection assays for SARS‐CoV‐2 Omicron variants including BA.1, BA.2, BA.3, BA.4, and BA.5. A 3D‐printed portable dual fluorescence visualization device and smartphone app are developed to enable point‐of‐care testing. This assay is rapid (within 90 min), highly sensitive (100 copies/reaction), and specific (identification of SNP) for SARA‐CoV‐2 Omicron variants. The ssLAMP method identifies five BA.5‐positive samples among 97 nasopharyngeal swab samples from the clinic, with a 100% concordance rate with Sanger sequencing. The ssLAMP assay system is expected to be utilized for on‐site, highly specific, and rapid visualization detection of SARS‐CoV‐2 and its variants, with great application potential in pathogen genotyping, early cancer screening, and other areas of SNP mutation detection.